Effects of Ionophorous Anticoccidial Drugs, Salinomycin and Lasalocid, on the Performance of Broiler Chicks and the Relationship of These Drugs to Supplementary Methionine - Ebrahimnezhad, Y.; Pourreza, J. (International Journal of Poultry Science, 2005)
This experiment was carried out to study the effect of ionophore drugs (salinomycin, lasalocid and their combination) on the performance of broiler chicks. Also their relationship with methionine (three levels) was evaluated. 1620 one-day-old commercial broiler chicks (Arian) were divided in to 108 groups, 15 chicks per group, and tested in a completely randomized design with 3x3x3 factorial experiment and three levels (0, recommended and 1.5 times recommended) of drugs and three levels (0, 0.1% and 0.2%) of supplemental methionine. The results indicated that these drugs reduced body weight gain significantly (P< 0.05) at 21 and 56 days of the experiment. Decreasing feed consumption and increasing feed conversion was significant (P< 0.05) due to lasalocid supplementation. Increasing drug level significantly (P< 0.05) reduced body weight gain and feed intake and feed conversion was increased at 21 to 42 and 0 to 56 days of the experiment. The effect of supplemental methionine on body weight of 42 days (P< 0.05) and feed conversion at 21 to 42 and 0 to 56 days (P< 0.01) were significant. The interactions between drug type and drug level on body weight gain, feed consumption and feed conversion were significant (P< 0.05). Lasalocid significantly (P< 0.05) increased water intake. Drugs did not affect litter moisture and mortality. The results showed that salinomycin was better than Lasalocid. Also supplemental methionine was not effective in compensating for the growth depression caused by ionophore drugs.